Intertextual Reception of Sinbad’s Story in American Film Adaptations - Mutiara Imania Mediana; Uki Sukiman (Universitas Islam Negeri Sunan Kalijaga, 2025)
This research examines how the United States received the story of Sinbad from the renowned Arab folklore, One Thousand and One Nights, and represented it in film. In this context, the term film is understood as a film text, referring to its narrative script, dialogues, and scenes that are analyzed through semiotic and linguistic approaches, rather than its technical audiovisual aspects. This research uses Hans Robert Jauss's reception theory to address the variations in reception found in Sinbad films produced in the United States and how the 'Horizon of Expectations' influences these variations. Among Jauss’s three approaches to reception analysis, this research adopts the intertextual approach. Intertextuality posits that each literary work cannot be separated from preceding literary works. This research shows that there are variations in reception across film genres, character portrayals, mysterious creatures featured, values represented in the story, and other aspects. These variations arise from the creativity of filmmakers, the demands of the film market, and efforts to adapt Sinbad's story more relatable to American audiences. Furthermore, the strong influence of Greek mythology and ancient Western seafaring tales further contributed to shaping these adaptations.